Communication, information, and knowledge in the pandemic by COVID-19 in Brazil - Campolino, Luana Moura [UNESP]; Bernardes, João Marcos [UNESP]; Alonso, Melissa Spröesser [UNESP]; Gómez-Salgado, Juan; Ruiz-Frutos, Carlos; Domínguez-Salas, Sara; Días, Adriano [UNESP] (Wolters Kluwer, 2022)
As coronavirus disease 2019 (COVID-19) is asserting itself as a health crisis, it is necessary to assess the knowledge and perceptions of people about the disease. The aim of this study is to assess the knowledge of the general population about COVID-19 and how the media influence this knowledge. This is a cross-sectional study with 5066 participants who answered an online questionnaire between April and May 2020. Data analysis was performed using descriptive statistics and logistic regression models. Over 75% have obtained a high degree of knowledge regarding signs, symptoms, and transmission, 95% stated to check the veracity of the information received, and also showed that the total knowledge about COVID-19 was associated with the level of instruction, with the perception of the quality of information disseminated by the media, and with the risk perception. Despite the high level of knowledge of participants, the results pointed to the need to reinforce information for individuals with less education and the importance of avoiding denialism that reduces the risk perception about COVID-19.
Keywords: coronavirus; COVID-19; epidemiology; health communication; information dissemination; knowledge; risk perception